THE INFLUENCE OF THE DEMONSTRATION METHOD OF MATHEMATICS LEARNING OUTCOMES DURING THE ONLINE PENDEMIC IN GRADE IV SDN CILAKU SERANG CITY - Ari Gunardi; Uvia Nursehah; Aditya Hikmawan (Amal Insani Foundation, 2022)
This research was conducted to find out the effect of the demonstration method on the results of learning mathematics during the online pandemic in the fourth grade of SDN Cilaku, Serang City. The type of research used by the researcher is experimental research, the experimental method with the type of true experiment. The form taken is Pretest-Posttest Control Group Design. The instrument used in this study was a test in the form of 30 multiple choice questions as well as student and teacher documentation. The student population studied in this study was 81 students with 40 students in class IV A and 41 students in IV B. Based on the results of the study, it can be seen that the results of cognitive learning in Mathematics before being treated using the demonstration method and tested using a pretest, the average value is 46.76. This value is included in the low category and the majority of students' pretest learning outcomes are 39 students in the low group or can be presented to 45.50%, which is possible because children are less interested in the usual lecture method used by the teacher. Meanwhile, after being treated using the demonstration method and doing a posttest, it can be seen that the average value changed to 73.82, and this is included in the fairly high category. The largest value is 100 (very high category). And the lowest value is 45.00 (very low category). The majority of students' posttest learning outcomes are in the high category, which is 45% or as many as 19 students. So it can be concluded that this research has the effect of using the demonstration method on learning outcomes of Mathematics in the material of flat shapes in fourth-grade students of SDN Cilaku, Serang City because it has increased the value of learning outcomes by as much as 70%. Keywords: Demonstration method, Learning outcomes